KONSUMSI LEMAK DAN KADAR KOLESTEROL HDL PASIEN DM TIPE 2 RAWAT JALAN DI RSUP SANGLAH DENPASAR - Putu Arie Tria Dewi; Yenny Moviana; Lely Cintari (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Abstract. Dyslipidemia characterized by hypertriglyceridemia, increase small dense LDL cholesterol and low HDL cholesterol levels, are common in patient with type 2 DM. This condition may increase the risk of cardiovascular diseases and increase the mortality rate of type 2 DM. Blood HDL cholesterol levels is a parameter that should be managed in type 2 DM.There were some studies reported that dietary intakes especially fat may associated to blood HDL cholesterol levels in type 2 DM patients. The study described the association of dietary fat intakes to blood HDL cholesterol levels in type 2 DM outpatients in Diabetic Center Sanglah General Hospital Denpasar. The study was observational and designed cross sectionally. It was conducted on June 2014. There were 43 subjects (19 males and 24 females). Most subjects were more than 45 years old (90.7%). There were more low educated, employee and have family history of DM subjects, 55.8%, 51.22%, and 58.1% respectively. Most subjects had low activity level and were obese 83.7% and 60.5% respectively. The result showed that most subjects (55,8%) with acceptable fat consumption level (25% of total energy) had excellent HDL cholesterol levels. There were no subjects with unacceptable fat consumption level (≥25% of total energy) had excellent HDL cholesterol levels. It is suggested to patient with type 2 DM to maintain their body weight, be more active, and keep dietary fat intakes no more than 25% (of total energy) to get excellent blood HDL cholesterol levels, and therefore lower the risk of cardiovascular diseases.Key words : HDL cholesterol level, fat consumption level.